Pulse oximetry as a tool to assess the level of acclimatisation and the effect of the training load on the body of an elite female runner during altitude training - Cervinka, P.; Kovarova, L.
The results of a case study on an elite female runner, participant of the World Championship and European Championship, are presented. We examined the feasibility of using a finger pulse oximeter to follow the acclimatisation process and training stress during mountain training workshops. We measured the subject`s blood saturation with oxygen, heart rate and perfusion index levels. The results demonstrated that periodic pulse measurements with a finger pulse oximeter can be used to monitor both the body response to acclimatisation at high altitudes and to the training load and that this is a promising approach to a rapid and reliable assessment of acclimatisation as well as to the monitoring of the body response to load.